Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas V SDN 66 Pontianak Kota - Reskita, Dela; Dessy Setyowati; Iir Nikmatul Fathonah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the cooperative model of the Teams Games Tournament type on the learning outcomes of fifth-grade students in Pancasila Education lessons at SD Negeri 66 Pontianak City. This research uses a quantitative approach with an experimental method. The type of research used is Quasi-Experimental Design, with a Nonequivalent Control Group Design. The sampling technique used is non-probability sampling. The data collection techniques used are tests and observations, while the data analysis techniques used include test item analysis, prerequisite tests, and hypothesis testing. The Independent T-test results show that the use of the teams games tournament cooperative learning model has a significant impact on student learning outcomes in Pancasila Education with a significance value of 0.042, so H0 is rejected and Ha is accepted because the sig. (2-tailed) value with a significance of 0.042 is smaller than 0.05. Therefore, it can be concluded that there is an effect of using the cooperative learning model of the teams games tournament type on the learning outcomes of Pancasila Education in grade V at SD Negeri 66 Pontianak Kota. According to this study, the impact of using the cooperative learning model of the teams games tournament type has an effect on student learning outcomes